Strategic management of tax disclosure: asymmetric timeliness of tax footnote modifications - Robert Ullmann; Sophia Wörle (Review of Managerial Science, 2024)
Previous studies have shown that qualitative disclosure contains information that facilitates the assessment of future firm outcomes. We first connect to this literature on early signals by showing that qualitative disclosure also specifically contains information about future ETR as one relevant firm outcome. Using the tax footnote from 10-K filings of all publicly traded U.S. firms over the period from 2000 to 2021, we show that year-over-year tax footnote modifications are an early signal of impending changes in ETR. When specifically considering the timeliness of this signal, we find that tax footnote modifications are associated with future changes in ETR at least three years in advance. Second, we investigate, as our main focus of analysis, asymmetry in timeliness. Here, we find that tax footnote modifications preceding increases in ETR occur relatively earlier (and are greater) than do (are) tax footnote modifications preceding decreases in ETR. We additionally use word lists to directly identify relevant underlying processes for changes in ETR and to investigate asymmetric timeliness conditional on the underlying process. Overall, our results indicate that firms strategically manage their tax disclosure in accordance with the ”accounting conservatism” hypothesis proposed by Basu ( 1997 ).
Keywords: H25; H29; H32; M41; 650; Financial disclosure; Tax footnote; Effective tax rate; Natural language processing; Disclosure similarity